Dietary Protein Requirement of Female Adults >65 Years Determined by the Indicator Amino Acid Oxidation Technique Is Higher Than Current Recommendations - Rafii, Mahroukh; Chapman, Karen; Owens, Jillian; Elango, Rajavel; Campbell, Wayne W; Ball, Ronald O; Pencharz, Paul B; Courtney-Martin, Glenda (The Journal of nutrition, 2015)
Studies on protein requirements in vulnerable groups such as older adults are few, and results are conflicting. The main objective of this study was to determine the protein requirements of free-living women >65 y by measuring the oxidation of l-[1-(13)C]phenylalanine to (13)CO2 in response to graded intakes of protein. Twelve subjects participated in the study, with protein intakes ranging from 0.2 to 2.0 g · kg(-1) · d(-1) for a total of 82 studies. The diets provided energy at 1.5 times each subject's resting energy expenditure and were isocaloric. Protein was given as an amino acid mixture on the basis of the egg protein pattern, except for phenylalanine and tyrosine, which were maintained constant across the protein intake amounts. All subjects were adapted for 2 d before the study day to a protein intake of 1.0 g · kg(-1) · d(-1). The mean protein requirement was determined by applying a mixed-effects change-point regression analysis to F(13)CO2 (label tracer oxidation in (13)CO2 breath), which identified a breakpoint in the F(13)CO2 in response to graded amounts of protein. The mean estimated average requirement (EAR) and upper 95% CI (approximating the RDA) protein requirement of women >65 y were 0.96 and 1.29 g · kg(-1) · d(-1), respectively. These estimates of protein requirements for older women are higher than the current EAR and RDA based on nitrogen balance data, which are 0.66 and 0.80 g · kg(-1) · d(-1), respectively. This trial was registered at clinicaltrials.gov as NCT01604980.